Nucleoside based self-assembling drugs for localized drug delivery - Skilling, Kathryn J.; Stocks, Michael J.; Kellam, Barrie; Ashford, Marianne; Bradshaw, Tracey; Burroughs, Laurence; Marlow, Maria (Wiley-VCH Verlag, 2018)
We have synthesized a range of gelators based on nucleoside analogues gemcitabine and lamivudine, characterizing representative gels from the series using rheology and TEM. Growth inhibition studies of gemcitabine derivatives confirmed the feasibility of these compounds as novel treatments, indicating the potential of nucleoside based gelators for localized drug delivery.